Does post-settlement support play a role in the success of land reform? : the case of resettlement beneficiaries in Namibia - Hoaes, Ingrid Emmy (Stellenbosch : University of Stellenbosch, 2010)
Thesis ((MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2010.